The cleansing of the temple in early medieval Northumbria. (18th November 2016) - O'Brien, Conor
Abstract: While the attitudes of Stephen of Ripon and Bede toward church-buildings have previously been contrasted, this paper argues that both shared a vision of the church as a holy place, analogous to the Jewish temple and to be kept pure from the mundane world. Their similarity of approach suggests that this concept of the church-building was widespread amongst the Northumbrian monastic elite and may partially reflect the attitudes of the laity also. The idea of the church as the place of eucharistic sacrifice probably lay at the heart of this theology of sacred place. Irish ideas about monastic holiness, traditional liturgical language and the native fascination with building in stone combined with an interest in ritual purity to give power to this use of the temple-image which went on to influence later Carolingian attitudes to churches.